2013
DOI: 10.1093/tropej/fmt076
|View full text |Cite
|
Sign up to set email alerts
|

Infant Overweight as Early Marker of Childhood Overweight in Brazil

Abstract: Infant overweight and rapid weight gain predict overweight and adiposity in childhood among low-income children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Postnatal FM accretion from 0 to 4 months was positively associated with FMI at 4 years. Several studies from high-income settings 17 , 20 , 54 have linked infant weight gain or fat accretion with higher levels of childhood adiposity, and one study in Brazil 55 showed consistent results. However, a few studies from low- and middle-income countries showed opposite association 21 23 in which weight gain associated with FFM but not with FM.…”
Section: Discussionmentioning
confidence: 88%
“…Postnatal FM accretion from 0 to 4 months was positively associated with FMI at 4 years. Several studies from high-income settings 17 , 20 , 54 have linked infant weight gain or fat accretion with higher levels of childhood adiposity, and one study in Brazil 55 showed consistent results. However, a few studies from low- and middle-income countries showed opposite association 21 23 in which weight gain associated with FFM but not with FM.…”
Section: Discussionmentioning
confidence: 88%
“…In the United States in 2012, 71% of adults aged 18 years and older reported drinking in the past year, and 51.3% of adults were current regular drinkers, defined as 12 or more drinks in the past year (Schiller, Lucas, Ward, & Peregoy, 2012). Older adults tend to decrease their total alcohol intake after retirement (Ferreira & Weems, 2008); in a 2008 national survey, approximately 40% of adults aged 65 years and older reported that they drank alcohol (Jardim-Botelho et al, 2014).…”
Section: Alcohol Consumption Patternsmentioning
confidence: 99%
“…It is possible that our sample was not large enough to detect an association, especially considering the low number of exclusively breastfed infants and the low number of overweight/obese children at age 2. It is also possible that other factors mitigated the relationship between early feeding and weight status at age 2, such as formula supplementation in year 1 of life, use of inappropriate foods and fluids early in life, or overfeeding or inappropriate types of foods before age 2 (Jardim‐Botelho et al, ; Saavedra, Deming, Dattilo, & Reidy, ). Finally, weight status using BMI may be a different indicator of overweight at age 2 than anthropometric measures.…”
Section: Discussionmentioning
confidence: 99%